An Analysis of Metafunction in Nick Vujicic's Motivational Speech Hear the Heart on YouTube - Seysar Dinda Nurul Pratiwi R.; Eva Solina Gultom (ELITE: Journal of English Language and Literature, 2022)
This study aims to analyze the language metafunctions in Nick Vujicic's Hear the Heart speech using Systemic Functional Linguistics (SFL) theory by M.A.K. Halliday and supported by other Systemic Functional Linguists theories. This study employed the qualitative method. 499 data clauses are investigated in this study. The result shows that in terms of ideational metafunction, the dominant process used by Nick was the mental process (33,07%) which indicates that he involved his senses to represent his experiences of the outer world as well as the inner world of his thoughts and feelings. In interpersonal metafunction, declarative mood (72,34%), high value of modality (38,50%), and second personal pronoun (58,62%) are the most frequently used in the speech, which shows his high commitment and certainty of the information he uttered and also to show his care and respect for the audience; thus, a close intimate relationship is maintained. Through textual metafunction, which is dominated by topical theme (52,70%), Nick attempts to get the audience's attention to focus on the message of what is being said and gives many statements to tell the audience about his experiences in life. To conclude, by using the three metafunctions, Nick could organize his language choice properly to create meaning and achieve his purpose in the speech.